Wood-bark-cambium relations during willow cloning and the mechanism of rooting in Salix discolor - Kefeli, Valentine; Leininger, Christopher; Mastalski, Shari; Rehn, Beth (İstanbul Kültür Üniversitesi, 2008)
The process of pussy willow (Salix discolor) propagation, or cloning, is an important biological process , which allows the increase of the amount of plant lets with the properties of the mother plants. Pussy willow has very weak dormancy. Therefore, the process of rootin g of stem cuttings may proceed ten month s in a year except September and October. We investigated the localization of the rooting process on the stem, performing surgery in the form of girdling of bark and partial stripping of bark with cambium from the stem. The process of rootin g was investigated. We observed that roots are formed only on the bark with cambium. If we strip the bark, no roots on the wood were observed . Rooted cuttings were subjected to preparation and we observed that roots were formed only on the bark - cambium complex . During the preparation of the stem, we did not separate bark from cambium and investigated this complex together.
Keywords: propagation; cloning; klonlama; yayılma